Contribution of the side resistance and tip resistance on the total axial load capacity of drilled shaft foundations - Abishdid, Caesar (2012)
The main loads applied on the drilled shafts are axial compressive loads. It is important to know how many percent of the maximum applied load will be shed in side friction and how much will be transferred to the base. Part of the axial load carrying capacity of the drilled shaft is resisted by the soil below the tip of the shaft which is tip resistance and the other part is resisted by the friction developed around the drilled shaft which is side resistance. The axial capacity of the drilled shaft foundation is influenced by the size of the drilled shaft, and soil characteristics. In this study, the effect of the size and soil characteristic will be investigated on the contribution of side resistance and end bearing capacity. Also, the study presents a three-dimensional finite element modeling of a drilled shaft subjected to axial load using ANSYS12. The top displacement and settlement of the drilled shaft are verified with analytical results. The soil profile is considered as Table 1 and for a drilled shaft with 7 ft diameter and 95 ft length the stresses in z-direction are calculated through the length of the shaft. There is a good agrrement between analythical and finite element results in contribution of side resistance and tip resistance for the drilled shaft.